A Validated Stability-Indicating LC Method for Orbifloxacin in the Presence of Degradation Products - Cazedey, Edith C. L. [UNESP]; Othman, Asma; Garg, Sanjay; Salgado, Hérida Regina Nunes [UNESP] (Bentham Science Publ Ltd, 2011)
A stability-indicating high-performance liquid chromatographic method was developed and validated for the determination of orbifloxacin in tablet dosage forms. Reversed-phase chromatography was performed on a Symmetry Shield RP-18 Waters (R), 250mmx4.6mm i.d., 5 mu m particle size column with 5% acetic acid: methanol (80:20, v/v) as mobile phase at a flow rate of 0.7 ml/min. PDA detection was performed at 290 nm. A well resolved peak was obtained for orbifloxacin at a retention time of approximately 7.9 min. For stress studies the drug was subjected to oxidation, hydrolysis, photolysis and thermal degradation. The developed method was validated as per ICH guidelines for the parameters such as system suitability, linearity, limit of quantification (LOQ), limit of detection (LOD), precision, accuracy, selectivity and robustness. Results obtained were found to be satisfactory. No interference from any excipients in the pharmaceutical dosage form or degradation products was observed.
Keywords: Degradation products; HPLC-UV; Liquid chromatography; Orbifloxacin; Stability-indicating method; Validation